Monitoring DNA replication in fission yeast by incorporation of 5-ethynyl-2'-deoxyuridine. - Hua, H; Kearsey, S (2011)
We report procedures to allow incorporation and detection of 5-ethynyl-2'-deoxyuridine (EdU) in fission yeast, a thymidine analogue which has some technical advantages over use of bromodeoxyuridine. Low concentrations of EdU (1 µM) are sufficient to allow detection of incorporation in cells expressing thymidine kinase and human equilibrative nucleoside transporter 1 (hENT1). However EdU is toxic and activates the rad3-dependent checkpoint, resulting in cell cycle arrest, potentially limiting its applications for procedures which require labelling over more than one cell cycle. Limited DNA synthesis, when elongation is largely blocked by hydroxyurea, can be readily detected by EdU incorporation using fluorescence microscopy. Thus EdU should be useful for detecting early stages of S phase, or DNA synthesis associated with DNA repair and recombination.